Long-term dynamics of tree of heaven (Ailanthus altissima) in central European forests - Julia Isler; Harald Bugmann; Marco Conedera; Timothy Thrippleton (European Journal of Forest Research, 2023)
Since the 1950s, the tree of heaven ( Ailanthus altissima ) has progressively invaded forests in southern Switzerland and is becoming a growing concern also north of the Alps. Recent studies have increased the understanding of the species’ ecology, but its role in long-term stand dynamics remains uncertain. Therefore, we simulated the long-term dynamics of unmanaged and managed forest stands in southern and northern Switzerland under current and future climate conditions (RCP8.5) using the forest gap model ForClim. Our results indicate that A. altissima will increase its presence in the short term (< 100 yrs), but does not gain dominance in the long term (> 200 yrs), confirming its pioneer character. Timber harvesting led to an increasing share of A. altissima compared to unmanaged stands. Overall, our findings suggest that in the long run, a competitive displacement of native dominant species by A. altissima appears unlikely, with the exception of drought-prone sites under strong climate change. Furthermore, our findings underline the importance of the frequency and intensity of forest management for the long-term abundance of A. altissima in forest stands.

Balancing disturbance risk and ecosystem service provisioning in Swiss mountain forests: an increasing challenge under climate change - Timothy Thrippleton; Christian Temperli; Frank Krumm; Reinhard Mey; Jürgen Zell; Sophie Stroheker; Martin M. Gossner; Peter Bebi; Esther Thürig; Janine Schweier (Regional Environmental Change, 2023)
Climate change severely affects mountain forests and their ecosystem services, e.g., by altering disturbance regimes. Increasing timber harvest (INC) via a close-to-nature forestry may offer a mitigation strategy to reduce disturbance predisposition. However, little is known about the efficiency of this strategy at the scale of forest enterprises and potential trade-offs with biodiversity and ecosystem services (BES). We applied a decision support system which accounts for disturbance predisposition and BES indicators to evaluate the effect of different harvest intensities and climate change scenarios on windthrow and bark beetle predisposition in a mountain forest enterprise in Switzerland. Simulations were carried out from 2010 to 2100 under historic climate and climate change scenarios (RCP4.5, RCP8.5). In terms of BES, biodiversity (structural and tree species diversity, deadwood amount) as well as timber production, recreation (visual attractiveness), carbon sequestration, and protection against gravitational hazards (rockfall, avalanche and landslides) were assessed. The INC strategy reduced disturbance predisposition to windthrow and bark beetles. However, the mitigation potential for bark beetle disturbance was relatively small (− 2.4%) compared to the opposite effect of climate change (+ 14% for RCP8.5). Besides, the INC strategy increased the share of broadleaved species and resulted in a synergy with recreation and timber production, and a trade-off with carbon sequestration and protection function. Our approach emphasized the disproportionally higher disturbance predisposition under the RCP8.5 climate change scenario, which may threaten currently unaffected mountain forests. Decision support systems accounting for climate change, disturbance predisposition, and BES can help coping with such complex planning situations.

Climate change impacts across a large forest enterprise in the Northern Pre-Alps: dynamic forest modelling as a tool for decision support - Timothy Thrippleton; Felix Lüscher; Harald Bugmann (European Journal of Forest Research, 2020)

Projecting Forest Dynamics Across Europe: Potentials and Pitfalls of Empirical Mortality Algorithms - Timothy Thrippleton; Lisa Hülsmann; Maxime Cailleret; Harald Bugmann (Ecosystems, 2020)

Overstorey–Understorey Interactions Intensify After Drought-Induced Forest Die-Off: Long-Term Effects for Forest Structure and Composition - Timothy Thrippleton; Harald Bugmann; Marc Folini; Rebecca S. Snell (Ecosystems, 2018)

Herbaceous Understorey: An Overlooked Player in Forest Landscape Dynamics? - Timothy Thrippleton; Harald Bugmann; Kathrin Kramer-Priewasser; Rebecca S. Snell (Ecosystems, 2016)

Bioclimatic niches of selected endemic Ixora species on the Philippines: predicting habitat suitability due to climate change - Cecilia Banag; Timothy Thrippleton; Grecebio Jonathan Alejandro; Björn Reineking; Sigrid Liede-Schumann (Plant Ecology, 2015)